Action Plan for BK Services in Pre-School Based on Parenting in Kindergarten Raudhatul Iman Padang - Wulansari, Afitri (EDUCTUM: Journal Research, 2023)
This research is motivated by the parenting style of parents that is wrong and is not applied to children as it should be in accordance with the child's development. This study aims to describe: 1) describe parenting styles. 2) Designing a guidance and counseling service program in pre-schools based on parenting styles.  This research was conducted using a quantitative descriptive method. The population in this study were all parents of students, totaling 33 people from 2 classes, namely class A and class B. While the sampling technique was carried out using saturated sampling technique or the entire sample was 33 people. research data obtained through questionnaires and processed using percentage techniques. Based on the results of the research that has been done, the following conclusions can be drawn: 1) Parenting as a whole is in the fairly frequent category, 2) The design of the guidance and counseling service program in pre-school based on parenting style will be carried out with 2 types services, namely basic services and responsive services. Based on the results of this study, it is recommended for counseling teachers or supervising teachers to be able to provide services to apply the right parenting style to children. For future researchers, it is recommended to use this research as a reference for implementing the programs created through this research